Effects of a Traditional versus an Alternative Strengthening Exercise Program on Shoulder Pain, Function and Physical Performance in Individuals with Subacromial Shoulder Pain: A Randomized Controlled Trial - Simon Schedler; Dennis Brueckner; Marco Hagen; Thomas Muehlbauer (MDPI AG, 2020)
A manual shoulder-training device may represent an alternative training device to improve symptoms and function in patients with subacromial shoulder pain by strengthening the external rotators. Thus, we examined the effects of a traditional versus an alternative strengthening exercise program on shoulder pain/function and physical performance in individuals with subacromial shoulder pain. Fifty-six adults with subacromial shoulder pain were randomly assigned to a passive control group (CON; n = 20), a traditional training group (TRA; n = 19), or an alternative training group (ALT; n = 17). Both training groups conducted a progressive home-based strengthening exercise program for the external rotators for eight weeks using elastic bands only (TRA group) or in combination with the shoulder-training device (Schulterhilfe®) (ALT group). Pre- and post-training assessment included measures of shoulder pain/function (i.e., shoulder pain and disability index (SPADI)) and physical performance (i.e., shoulder flexibility, maximal isometric strength, and strength endurance). We found significant test × group interactions in most of the investigated variables. Post hoc analyses showed significant training-related improvements for proxies of shoulder pain/function, shoulder flexibility, maximal isometric strength, and strength endurance in favor of the ALT and TRA group in comparison to the CON group. Further, larger and more frequent effects were found for the ALT compared to the TRA group. Measures of shoulder pain/function and physical performance can be significantly improved by both training regimens in individuals with subacromial shoulder pain. However, strength training using elastic bands with the manual shoulder device (ALT group) as compared to elastic bands (TRA group) only was more effective and may thus be a recommendable alternative in order to mitigate subacromial shoulder pain.